1995
DOI: 10.1210/jcem.80.4.7714095
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose adrenocorticotropin test reveals impaired adrenal function in patients taking inhaled corticosteroids.

Abstract: The aim of the present study was to examine the use of low-dose ACTH-(1-24) stimulation for assessment of adrenal function and the detection of mild adrenal insufficiency. The criteria for normal response to ACTH-(1-24) are a peak cortisol level of more than 500 nmol/L (18.1 micrograms/dL) and an increment of the cortisol level above the basal one of more than 200 nmol/L (7.2 micrograms/dL). These criteria were satisfied by 32 of 33 healthy children and adults subjected to an ACTH-(1-24) dose 500 times lower (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(42 citation statements)
references
References 17 publications
2
39
1
Order By: Relevance
“…In the case of patients with mild adrenal insufficiency, a higher stimulus could increase the risk of falsenegatives (good responders). Thus, our data seem coherent with the statement of several authors 6,15,23,24,27 about the higher sensitivity of LDT in detecting cases of secondary adrenal insufficiency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the case of patients with mild adrenal insufficiency, a higher stimulus could increase the risk of falsenegatives (good responders). Thus, our data seem coherent with the statement of several authors 6,15,23,24,27 about the higher sensitivity of LDT in detecting cases of secondary adrenal insufficiency.…”
Section: Discussionsupporting
confidence: 92%
“…4 Likewise, some authors have recently demonstrated that serum cortisol response to 1 µ g is similar to that obtained with 250 µ g in normal subjects and pointed out that the LDT has a greater diagnostic sensitivity than the HDT in secondary adrenal insufficiency. [5][6][7][8][9] However, considerable debate exists in the literature about the reliability of both tests and whether LDT is better than HDT in the evaluation of secondary adrenal insufficiency. 10 Little is known with regard to the profiles of ACTH(1-24) and ACTH(1-39) after HDT and LDT in healthy volunteers, and even less about the elimination rate of ACTH in humans after these tests.…”
Section: Introductionmentioning
confidence: 99%
“…The application of different response criteria (Broide et al, 1995;Hurel et al, 1991) to the cortisol responses in our healthy group and CFS cohort revealed marked inconsistencies in 'pass-fail' patterns of response. This may be explained by testing time differences-Hurel performed his study at 0900 h when basal cortisol values can be expected to be higher than the early afternoon samples of this study.…”
Section: Discussionmentioning
confidence: 73%
“…An incremental cortisol response of 250 nmol/l cortisol was found to distinguish best between the two groups. Results were also analysed on the basis of response criteria forwarded by Broide et al (1995) and Hurel et al (1996) of a peak response of > 500 nmol/l and > 600 nmol/l respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, final growth impairthat of patients who had never been treated with corticosteroids. [45][46][47][48] The systemic activity of ICS is determined by several factors, including corticosteroid receptor potency, receptor binding affini- Finally, from this metaing, the circadian rhythm of cortisol, and free urine cortisol excreanalysis it emerged that there is no correlation between dose and tion.…”
Section: Long-term Effects Of Icsmentioning
confidence: 99%